2012
DOI: 10.1242/jeb.066167
|View full text |Cite
|
Sign up to set email alerts
|

Within-lifetime trade-offs but evolutionary freedom for hormonal and immunological traits: evidence from mice bred for high voluntary exercise

Abstract: SUMMARYChronic increases in circulating corticosterone (CORT) generally suppress immune function, but it is not known whether evolved increases necessarily have similar adverse effects. Moreover, the evolution of immune function might be constrained by the sharing of signaling molecules, such as CORT, across numerous physiological systems. Laboratory house mice (Mus domesticus Linnaeus) from four replicate lines selectively bred for high voluntary wheel running (HR lines) generally had baseline circulating COR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 81 publications
4
19
1
Order By: Relevance
“…Malisch et al showed that, although HR and C mice did not differ statistically in the ability to clear an intestinal nematode infection (Nippostrongylus brasiliensis), an analysis of the eight line means revealed a negative relationship between clearance ability and baseline CORT levels, supporting the hypothesis that CORT has immunosuppressive effects (Malisch et al, 2009a). More recently, a study by Downs and colleagues also found no statistical difference between the HR and C lines following an immune challenge with lipopolysaccharide (Downs et al, 2012). Thus, evidence to date indicates that HR and C mice may be capable of similar immune responses to infection.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Malisch et al showed that, although HR and C mice did not differ statistically in the ability to clear an intestinal nematode infection (Nippostrongylus brasiliensis), an analysis of the eight line means revealed a negative relationship between clearance ability and baseline CORT levels, supporting the hypothesis that CORT has immunosuppressive effects (Malisch et al, 2009a). More recently, a study by Downs and colleagues also found no statistical difference between the HR and C lines following an immune challenge with lipopolysaccharide (Downs et al, 2012). Thus, evidence to date indicates that HR and C mice may be capable of similar immune responses to infection.…”
Section: Introductionmentioning
confidence: 98%
“…Assuming competing energetic demands and a limited energy supply or ability to process food, we predicted that parasitized animals would reduce voluntary activity levels to allow for an upregulation of immune function. A long-term experiment selectively breeding mice for high voluntary wheel running Rhodes et al, 2005;Garland et al, 2011a;Garland et al, 2011b) is particularly wellsuited to studies involving possible trade-offs between locomotion and other metabolically costly functions, including immune responses (Malisch et al, 2009a;Downs et al, 2012). Prior work shows that voluntary running can account for substantial fractions of daily energy expenditure (Rezende et al, 2009), and running in high voluntary wheel running (HR) lines has remained unchanged for >40 generations, despite continued selection, suggesting that it has reached an upper limit (Rezende et al, 2009;Kolb et al, 2010;Careau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations